Mimicking ‘broken windows’ policing in post-soviet cities: expanding social control in uncertain times - Marat, Erica (Policing and society, 2019)
Kazakhstan and Ukraine are the two latest adopters of the broken windows theory of policing first applied in New York City in the 1990s. Both countries embraced the practice despite its declining popularity and widespread criticism in the West. This article explores why and how broken windows policing is mimicked in both countries’ largest cities - Almaty and Kyiv. It shows that there are striking similarities in how various order-maintenance policing initiatives rose to prominence in Western urban areas and later in the post-Soviet context. The expansion of the middle class and the rapidly changing demography of urban areas due to socio-economic transformations popularised this norm-setting style of policing. By expanding policing of disorderly behaviours, both countries also tried to mould the type of citizens appropriate for a state with grand geopolitical ambitions. Kazakhstan and Ukraine sought to improve their regional and global rankings by creating a more orderly domestic environment.